ASEAN AND INDONESIA’S POLICY AGAINST WASTE IMPORT IN INDONESIA - Surya Tri Putri Dalapang; Inggrid Janna Bella Sihaloho; Febriana Christianti; Dhiva Aribah Setyaningrum; Diva Putri Kaloko (Sociae Polites, 2021)
Environmentalism has in common with other theories when it comes to making a movement. This theory talks about the environment, and its relationship with humans, how human behavior can impact the environment around it. This journal will discuss waste import as the main topic. Many people still do not know about the waste import activities carried out by the Indonesian. Therefore, we present data that describes how the process of these activities occurs, in relation to theory, other problems arising from the incident, Indonesian government policies and their implementation, as well as the right solutions that can be taken to prevent or even solve the problem. Keywords: Environmentalism, Waste import, Policy, Government, Implementation